Operational Modal Analysis and the Performance Assessment of Vehicle Suspension Systems - L. Soria; B. Peeters; J. Anthonis; H. Van der Auweraer (Shock and Vibration)
Comfort, road holding and safety of passenger cars are mainly influenced by an appropriate design of suspension systems. Improvements of the dynamic behaviour can be achieved by implementing semi-active or active suspension systems. In these cases, the correct design of a well-performing suspension control strategy is of fundamental importance to obtain satisfying results. Operational Modal Analysis allows the experimental structural identification in those that are the real operating conditions: Moving from output-only data, leading to modal models linearised around the more interesting working points and, in the case of controlled systems, providing the needed information for the optimal design and verification of the controller performance. All these characters are needed for the experimental assessment of vehicle suspension systems. In the paper two suspension architectures are considered equipping the same car type. The former is a semi-active commercial system, the latter a novel prototypic active system. For the assessment of suspension performance, two different kinds of tests have been considered, proving ground tests on different road profiles and laboratory four poster rig tests. By OMA-processing the signals acquired in the different testing conditions and by comparing the results, it is shown how this tool can be effectively utilised to verify the operation and the performance of those systems, by only carrying out a simple, cost-effective road test.